2004
DOI: 10.1213/01.ane.0000113556.40345.2e
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Gastrointestinal Complications After Cardiopulmonary Bypass: Can Outcome Be Predicted from Preoperative Risk Factors?

Abstract: We identified the preoperative and intraoperative predictors associated with an increased incidence of postoperative gastrointestinal complications after cardiac surgery using cardiopulmonary bypass. Because these complications are associated with frequent morbidity and mortality, these predictors may be helpful in identifying patients at increased risk so that risk stratification can be modified and perioperative management can be appropriately adjusted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 18 publications
1
41
1
1
Order By: Relevance
“…The pathophysiology of GI complications following cardiac surgery has not been well elucidated. Low cardiac output resulting in visceral hypoperfusion and mucosal ischemia and necrosis has been suggested on by multiple authors [1,9]. Multiple risk factors have been considered significant with GI complications including age greater than 70 years, long duration of cardiopulmonary bypass, blood transfusion, reoperation, ischemic heart disease, renal failure, and low cardiac index [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of GI complications following cardiac surgery has not been well elucidated. Low cardiac output resulting in visceral hypoperfusion and mucosal ischemia and necrosis has been suggested on by multiple authors [1,9]. Multiple risk factors have been considered significant with GI complications including age greater than 70 years, long duration of cardiopulmonary bypass, blood transfusion, reoperation, ischemic heart disease, renal failure, and low cardiac index [10].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal (GI) complications have been reported to occur after cardiac surgery 0.29% -5.5% and are associated with mortality rates of 11% -72% [1][2][3][4]. The high mortality in these patients has been attributed to delayed diagnosis and treatment of GI complications.…”
Section: Introductionmentioning
confidence: 99%
“…The transfusion of bank blood and the use of pharmacologic cardiovascular support were identified as independent intraoperative risk factors (7). Improvements in surgical techniques such as off-pump surgery do not seem to have made any significant impact on the incidence or prognosis of adverse GI outcome (8).…”
Section: Predictorsmentioning
confidence: 99%
“…Although clinical and experimental trials have showed that the splanchnic injury is in most of the cases transient and selflimiting, manifest heart insufficiency, whenever in the presence or absence of the atheromatous disease, contributes to a higher incidence of intestinal complications after CPB (11,12). Constricting (e.g., thromboxane A 2 , angiotensin II, and endothelin-1), vasodilating (e.g., nitric oxide [NO]), and inflammatory hormones (cytokines) released locally by the endothelium, nerve terminals, platelets, and leukocytes have been suggested to participate in heart failure (HF)-induced vascular remodeling (13) and, may subsequently exacerbate the post-CPB mesenteric damage.…”
Section: Introductionmentioning
confidence: 99%